2015
DOI: 10.1080/19443994.2015.1100879
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic membrane bioreactors—a mini review with emphasis on industrial wastewater treatment: applications, limitations and perspectives

Abstract: Anaerobic membrane bioreactors (AnMBRs) are increasingly being used in industrial wastewater treatment as the technology represents a cost-effective alternative to that based on aerobic processes. Not only AnMBRs are highly efficient in reducing chemical oxygen demand but the organic matter removed is transformed into a useful energy source-biogas. AnMBRs produce effluent that is free of solids and pathogens and rich in nutrients, while occupying a small footprint. As the membrane retains biomass, AnMBRs enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 117 publications
(180 reference statements)
2
43
0
1
Order By: Relevance
“…Studies have shown that at elevated TMP and flux, the membrane could easily polarize and the tendency for bio-flocs disintegration is high. This habitually resulted in excessive operational energy requirements [118][119][120]. The findings of the previous studies on MBR configurations are summarized in Table 2.…”
Section: Side-stream Configuration (Ss-mbr)mentioning
confidence: 99%
“…Studies have shown that at elevated TMP and flux, the membrane could easily polarize and the tendency for bio-flocs disintegration is high. This habitually resulted in excessive operational energy requirements [118][119][120]. The findings of the previous studies on MBR configurations are summarized in Table 2.…”
Section: Side-stream Configuration (Ss-mbr)mentioning
confidence: 99%
“…PSDs stabilize sludge to control odors while also reducing pathogens [3]. In addition to PSDs, AnMBRs have been widely incorporated into the anaerobic biological wastewater treatment process because of their solid-liquid separation and high effluent quality [4]. Due to their high operation stability, AnMBRs are suitable for treating wastewater with a high content of COD and suspended solids, high salinity, and large variations of flow and composition, even in the presence of fat, oil, and grease or inhibitory compounds [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As it can be seen from comparison of the data in Tables 4 and 6, as well as in Fig. 5, only introduction of the reagent allowed achieving the necessary degree of purification from phosphates (98.6 % in series of experiments [10][11][12]. Termination of reagent dosing has resulted in an increase in phosphate content in a purified sewer in excess of the established standard for discharge (Table 4, series of experiments [17][18][19].…”
Section: Discussion Of Results Of Experimental Research Into the Procmentioning
confidence: 84%
“…The authors of work [10] proposed the technology of application of the anaerobic membrane bioreactor. This technology proved to be very effective in reducing the chemical oxygen demand (COD), in this case, the removed organic substance turns into a useful energy source -biogas.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%